Stressful social relations and mortality: a prospective cohort study. Issue 8 (8th May 2014) - Lund, Rikke; Christensen, Ulla; Nilsson, Charlotte Juul; Kriegbaum, Margit; Hulvej Rod, Naja
Abstract : Background: Few studies have examined the relationship between stressful social relations in private life and all-cause mortality. Objective: To evaluate the association between stressful social relations (with partner, children, other family, friends and neighbours, respectively) and all-cause mortality in a large population-based study of middle-aged men and women. Further, to investigate the possible modification of this association by labour force participation and gender. Methods: We used baseline data (2000) from The Danish Longitudinal Study on Work, Unemployment and Health, including 9875 men and women aged 36–52 years, linked to the Danish Cause of Death Registry for information on all-cause mortality until 31 December 2011. Associations between stressful social relations with partner, children, other family, friends and neighbours, respectively, and all-cause mortality were examined using Cox proportional hazards models adjusted for age, gender, cohabitation status, occupational social class, hospitalisation with chronic disorder 1980–baseline, depressive symptoms and perceived emotional support. Modification by gender and labour force participation was investigated by an additive hazards model. Results: Frequent worries/demands from partner or children were associated with 50–100% increased mortality risk. Frequent conflicts with any type of social relation were associated with 2–3 times increased mortality risk. Interaction between labour force participation and worries/demands (462 additional cases per 100 000 person-years, p=0.05) and conflicts with partner (830 additional cases per 100 000 person-years, p<0.01) was suggested. Being male and experiencing frequent worries/demands from partner produced 135 extra cases per 100 000 person-years, p=0.05 due to interaction. Conclusions: Stressful social relations are associated with increased mortality risk among middle-aged men and women for a variety of different social roles. Those outside the labour force and men seem especially vulnerable to exposure.